A Systematic Phylogenomic Classification of the Multidrug and Toxic Compound Extrusion Transporter Gene Family in Plants - Nimmy, Manduparambil Subramanian; Kumar, Vinod; Suthanthiram, Backiyarani; Subbaraya, Uma; Nagar, Ramawatar; Bharadwaj, Chellapilla; Jain, Pradeep Kumar; Krishnamurthy, Panneerselvam (Frontiers in Plant Science, 2022)
Multidrug and toxic compound extrusion (MATE) transporters comprise a multigene family that mediate multiple functions in plants through the efflux of diverse substrates including organic molecules, specialized metabolites, hormones, and xenobiotics. MATE classification based on genome-wide studies remains ambiguous, likely due to a lack of large-scale phylogenomic studies and/or reference sequence datasets. To resolve this, we established a phylogeny of the plant MATE gene family using a comprehensive kingdom-wide phylogenomic analysis of 74 diverse plant species. We identified more than 4,000 MATEs, which were classified into 14 subgroups based on a systematic bioinformatics pipeline using USEARCH, blast+, and synteny network tools. Our classification was performed using a four-step process, whereby MATEs sharing ≥ 60% protein sequence identity with a ≤ 1E-05 threshold at different sequence lengths (either full-length, ≥ 60% length, or ≥ 150 amino acids) or retaining in the similar synteny blocks were assigned to the same subgroup. In this way, we assigned subgroups to 95.8% of the identified MATEs, which we substantiated using synteny network clustering analysis. The subgroups were clustered under four major phylogenetic groups and named according to their clockwise appearance within each group. We then generated a reference sequence dataset, the usefulness of which was demonstrated in the classification of MATEs in additional species not included in the original analysis. Approximately 74% of the plant MATEs exhibited synteny relationships with angiosperm-wide or lineage-, order/ family-, and species-specific conservation. Most subgroups evolved independently, and their distinct evolutionary trends were likely associated with the development of functional novelties or the maintenance of conserved functions. Together with the systematic classification and synteny network profiling analyses, we identified all the major evolutionary events experienced by the MATE gene family in plants. We believe that our findings and the reference dataset provide a valuable resource to guide future functional studies aiming to explore the key roles of MATEs in different aspects of plant physiology. Our classification framework can also be readily extended to other (super)families.